2014
DOI: 10.1155/2014/145747
|View full text |Cite
|
Sign up to set email alerts
|

Repeated High Intensity Bouts with Long Recovery: Are Bicarbonate or Carbohydrate Supplements an Option?

Abstract: The effects of varying recovery modes and the influence of preexercise sodium bicarbonate and carbohydrate ingestion on repeated high intensity performance, acid-base response, and recovery were analyzed in 12 well-trained males. They completed three repeated high intensity running bouts to exhaustion with intervening recovery periods of 25 min under the following conditions: sodium bicarbonate, active recovery (BIC); carbohydrate ingestion, active recovery (CHO); placebo ingestion, active recovery (ACTIVE); p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Stoggl et al, investigated the supplementation in the performance under these condition: a. carbohydrate supplementation in active recovery, b. bicarbonate supplementation in active recovery, c. placebo supplementation in active recovery and d. placebo supplementation in passive recovery, in a protocol of three sprints during a treadmill test. Results showed that the strategies of supplementation when compared to the active (placebo) condition did not present significant differences in the increase of performance; on the contrary, when compared to the two placebo conditions, there was a reduction in placebo (passive) performance (Stöggl, Torres-Peralta, Cetin, & Nagasaki, 2014), which corroborates our findings. Evidence of the significant influence of placebo on performance of number repetition and total load has recently been reported by Marocolo et al that compared the ischemic preconditioning and the placebo maneuver with control group in thirteen men in the resistance exercise (Moacir Marocolo et al, 2016).…”
Section: Dicussionsupporting
confidence: 89%
“…Stoggl et al, investigated the supplementation in the performance under these condition: a. carbohydrate supplementation in active recovery, b. bicarbonate supplementation in active recovery, c. placebo supplementation in active recovery and d. placebo supplementation in passive recovery, in a protocol of three sprints during a treadmill test. Results showed that the strategies of supplementation when compared to the active (placebo) condition did not present significant differences in the increase of performance; on the contrary, when compared to the two placebo conditions, there was a reduction in placebo (passive) performance (Stöggl, Torres-Peralta, Cetin, & Nagasaki, 2014), which corroborates our findings. Evidence of the significant influence of placebo on performance of number repetition and total load has recently been reported by Marocolo et al that compared the ischemic preconditioning and the placebo maneuver with control group in thirteen men in the resistance exercise (Moacir Marocolo et al, 2016).…”
Section: Dicussionsupporting
confidence: 89%
“…Race analyses and practical observations of cross-country skiing competitions indicate that although some skiers are very good during the first half of the prologue, they cannot sustain their level of performance throughout the remainder of the competition (unpublished observation). Recently, a few studies have addressed the effects of varying recovery modes on repeated efforts in the context of sprint skiing [ 55 , 59 ]. Although active recovery was associated with a slightly, but significantly, greater effect on aerobic turnover than passive recovery [ 55 ], roller-skiing performance (two 800-m heats on a treadmill) using the G3 (V2) technique was similar.…”
Section: Discussionmentioning
confidence: 99%
“…Although active recovery was associated with a slightly, but significantly, greater effect on aerobic turnover than passive recovery [ 55 ], roller-skiing performance (two 800-m heats on a treadmill) using the G3 (V2) technique was similar. On the other hand, Stöggl and colleagues [ 59 ] observed that passive recovery resulted in greater decrements during high intensity runs to exhaustion compared to active recovery strategies implemented with or without supplementation. In combination, these two studies suggests a benefit of active versus passive recovery strategies during sprint skiing competitions, although further research is obviously needed to determine the optimal dosage and explore alternative recovery strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the SBS effect will not be reduced by a moderate warm-up, and a moderate warm-up will not affect the time-to-peak for blood pH and HCO 3 − . Most studies show that SBS improves energy metabolism and ionic regulation (Egger et al, 2014;Heibel et al, 2018;Hilton et al, 2020;Stöggl et al, 2014). The significant elevation of blood pH and HCO3 − concentration following SBS in the pretest and TTrun were of similar magnitude compared with these studies.…”
Section: Discussionmentioning
confidence: 58%